Persepsi Mahasiswa Terhadap Pembelajaran Daring Pada Masa Pandemi COVID 19 Di Jurusan Administrasi Bisnis Politeknik Negeri Banjarmasin - huwaida, hikmayanti; Rofi'i, Rofi'i; Imelda, Sri (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
As an effort to prevent the spread of Coronavirus transmission, education policy adjustments were made at Banjarmasin State Polytechnic. In an effort to support breaking the chain of distribution of Covid 19, Banjarmasin State Polytechnic applies online learning. The research objective is to determine the effect of perceived enjoyment, perceived ease of use, and actual technology use together and partially on student satisfaction in online learning during the Covid 19 pandemic at the Banjarmasin State Polytechnic Business Administration Department. This research is descriptive and verification with a quantitative approach. Data was taken at Banjarmasin State Polytechnic Business Administration Department. The population is the students of Banjarmasin State Polytechnic Business Administration Department. The unit of analysis is Banjarmasin State Polytechnic Business Administration students as many as 171 people. Data collection techniques are done by distributing questionnaires or questionnaires. Data analysis techniques used multiple linear regression analysis. The results showed that; 1) Perceived enjoyment, perceived ease of use, and actual technology use together positively and significantly influence student satisfaction by 55.7%; 2) Partially perceived enjoyment has a significant effect, perceived ease of use is insignificant, and actual technology use has a positive and significant effect on student satisfaction in online learning during Covid 19 at the Banjarmasin State Polytechnic Business Administration Department.